2019
DOI: 10.24154/jhs.2019.v14i02.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Cultivars of Tuberose (Polianthes tuberosa L.) under Humid agro Climatic conditions of Goa

Abstract: Tuberose (Polianthes tuberosa L.) is one of the most important tropical bulbous-ornamental cultivated for production of long-lasting flowers spikes. Adaptation and acclimatization of different cultivars under humid agro-climatic conditions of Goa are to be confirmed for their better performance. The present investigation was conducted to evaluate the performance of tuberose cultivars under agro-climatic conditions of Goa during 2014- 2017. Five single and six double cultivars of tuberose were evaluated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Variation among the tuber ose cultivars for the shelf life may be attributable to the hereditary traits, which is further interpreted by prevailing climatic conditions. Safeena et al (2019) reported the presence of genotypic variation in post-harvest life of tuberose.…”
Section: Resultsmentioning
confidence: 99%
“…Variation among the tuber ose cultivars for the shelf life may be attributable to the hereditary traits, which is further interpreted by prevailing climatic conditions. Safeena et al (2019) reported the presence of genotypic variation in post-harvest life of tuberose.…”
Section: Resultsmentioning
confidence: 99%
“…Because of aromatic compounds, they are mostly used in the perfume industry. Furthermore, the plant comprises a variety of secondary metabolites, including steroid glycosides and flavonoids, whereas the flower mostly contains terpenoid derivatives and benzoid (Fan et al, 2018;Safeena et al, 2019;Alghuthaymi et al, 2021). As a result, there is an urgent need for novel antibacterial drugs to combat the increasing range of illnesses.…”
Section: Introductionmentioning
confidence: 99%